Social Inequality and Digital Economic Transformation: A Study of Access, Opportunity, and Social Justice in Urban Societies - Ahmad Mubarok (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This study aims to analyze the social inequalities arising from the digital economic transformation in urban areas, focusing on aspects of access, opportunity, and social justice. Using a qualitative approach based on literature, this study examines various scientific sources discussing the digital divide phenomenon, shifts in economic structure, and their implications for social welfare. The results of the study indicate that the development of the digital economy in large cities is not fully inclusive, as significant gaps remain in terms of access to technology, digital literacy, and the adaptability of lower-middle-class communities. This phenomenon demonstrates a new reproduction of increasingly complex social inequality, where highly educated groups with technological capital gain greater benefits from the digital economic system. Furthermore, the emergence of the gig economy creates new forms of job instability and social uncertainty among digital workers. This study emphasizes the importance of public policies that emphasize social justice, equitable distribution of digital infrastructure, and strengthening technological literacy as strategic steps to realize an inclusive and sustainable digital economy. Thus, digital transformation needs to be directed not only at economic efficiency, but also at social welfare and equal opportunities for all levels of urban society